The gender gap in mathematics: Evidence from a middle-income country - Prashant Bharadwaj; Giacomo De Giorgi; David Hansen; Christopher Neilson (Federal Reserve Bank of New York, 2015)
Using a large administrative data set from Chile, we find that, on average, boys perform better than girls in mathematics. In this paper, we document several features of their relative performance. First, we note that the gender gap appears to increase with age (it doubles between fourth grade and eighth grade). Second, we test whether commonly proposed explanations such as parental background and investment in the child, unobserved ability, and classroom environment (including teacher gender) help explain a substantial portion of the gap. While none of these explanations help in explaining a large portion of the gender gap, we show that boys and girls differ significantly in perceptions about their own ability in math. Conditional on math scores, girls are much more likely to state that they dislike math, or find math difficult, compared to boys. We highlight differences in self-assessed ability as areas for future research that might lead to a better understanding of the gender gap in math.
Keywords: I00; I25; J16; 330; gender gap; education; middle-income countries